Circ-MFN2 Positively Regulates the Proliferation, Metastasis, and Radioresistance of Colorectal Cancer by Regulating the miR-574-3p/IGF1R Signaling Axis - Liu, Defeng; Peng, Shihao; Li, Yangyang; Guo, Tao (Frontiers in Genetics, 2021)
Numerous studies have shown that the expression of circular RNA (circRNA) is closely related to the malignant progression of cancer. However, the role of circ-MFN2 in colorectal cancer (CRC) is unclear. Our study aims to explore the role and mechanism of circ-MFN2 in CRC progression. The relative expression levels of circ-MFN2, microRNA (miR)-574-3p and insulin-like growth factor 1 receptor (IGF1R) were detected by quantitative real-time polymerase chain reaction (qRT-PCR). Cell viability was determined using 3-(4, 5-dimethyl-2 thiazolyl)-2, 5-diphenyl-2-H-tetrazolium bromide (MTT) assay. The colony number and radioresistance of cells were assessed using colony formation assay. Moreover, the migration and invasion of cells were measured using transwell assay. Tumor xenograft model was constructed to evaluate the effect of circ-MFN2 knockdown on CRC tumor growth. Furthermore, dual-luciferase reporter assay was used to verify the interaction between miR-574-3p and circ-MFN2 or IGF1R. In addition, the protein level of IGF1R was evaluated by western blot (WB) analysis. Circ-MFN2 expression was elevated in CRC tissues and cells. Knockdown of circ-MFN2 restrained the proliferation, migration, invasion, and radioresistance of CRC cells in vitro. Furthermore, silenced circ-MFN2 also reduced the tumor volume and weight of CRC in vivo. MiR-574-3p could be sponged by circ-MFN2, and its inhibitor reversed the suppression effect of circ-MFN2 silencing on CRC progression. Moreover, IGF1R was a target of miR-574-3p, and its overexpression reversed the inhibition effect of miR-574-3p mimic on CRC progression. In addition, circ-MFN2 could positively regulate IGF1R expression by sponging miR-574-3p. Our results revealed that circ-MFN2 promoted the proliferation, metastasis and radioresistance of CRC through regulating the miR-574-3p/IGF1R axis, suggesting that circ-MFN2 might be a novel therapeutic biomarker for CRC.